PENGARUH MORAL WAJIB PAJAK DAN DEMOGRAFI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DENGAN SANKSI PERPAJAKAN SEBAGAI PEMODERASI - Astuti, Tri; Panjaitan, Ingrid (Media Akuntansi Perpajakan, 2018)
The purpose of this study was to examine the moral influence of taxpayers and taxpayer demographics on UMKM taxpayer compliance with taxation sanctions as moderating variables. This research was carried out in all Micro, Small and Medium Enterprises (UMKM) in North Jakarta. Sampling technique using Quota Sampling Method. This method requires taking as many samples as the amount determined by the researcher as a target that must be met. The sample in this study was 360 in the UMKM field in North Jakarta. Data collection method uses a questionnaire method. Data testing in this study uses multiple regression and moderation tests. Data processing was done using Partial Least Square (PLS) version 3.00. The statistical method used is the coefficient path. The results of this study indicate that the taxpayer's morality has a significant positive effect on UMKM taxpayer compliance, taxpayer demographics have a significant positive effect on UMKM taxpayer compliance, tax sanctions have a significant positive effect on UMKM taxpayer compliance, moderation of tax sanctions has a significant positive effect on the taxpayer's moral UMKM taxpayer compliance, and moderation of tax sanctions has a significant negative impact on taxpayer demographics on UMKM taxpayer compliance.Keywords: Taxpayer Moral, Taxpayer Demographics, UMKM Taxpayer Compliance, Tax Sanctions.